Applied Cryptography and Network Security 14th International Conference, ACNS 2016, Guildford, UK, June 19-22, 2016. Proceedings - Manulis, Mark; Sadeghi, Ahmad-Reza; Schneider, Steve (Security and Cryptology, 2016)
This book constitutes the refereed proceedings of the 14th International Conference on Applied Cryptography and Network Security, ACNS 2016, held in Guildford, UK. in June 2016. 5. The 35 revised full papers included in this volume and presented together with 2 invited talks, were carefully reviewed and selected from 183 submissions. ACNS is an annual conference focusing on innovative research and current developments that advance the areas of applied cryptography, cyber security and privacy. .